Peningkatan Keterampilan Pembuatan Presentasi Berbasis Kecerdasan Buatan Pada Pemuda Karang Taruna Duri Pulo Jakarta Pusat - Wahyu Pramusinto; Ika Susanti; Ferdiansyah; Putri Hayati; Sejati Waluyo (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The Karang Taruna youth organization plays a vital role as a social driver in urban areas, specifically, the Duri Pulo chapter in Central Jakarta mobilizes young people to participate actively in various social activities. However, many members face challenges in translating their ideas and work programs into communicative visual presentations due to limited graphic design skills and time constraints. This Community Service Program (PKM) aims to enhance the digital literacy of these youths through training on creating presentations using artificial intelligence (AI). The initiative comprises four stages: preparation, an introduction to basic AI concepts, hands-on practical training, and a final phase of evaluation and mentoring. Attended by Karang Taruna administrators and youth members, the training proceeded smoothly and was met with great enthusiasm. Through hands-on practice, participants successfully grasped the utility of AI and learned to craft prompts to generate professional visual presentation designs. Participants are now capable of independently designing interactive presentations within a short timeframe. The training proved effective in boosting the youths' creativity, work efficiency, and confidence in communicating their program initiatives to the community and stakeholders.